THE CORRELATION BETWEEN STUDENT’S ACTIVITIES IN STORYTELLING WITH THEIR INTEREST IN SPEAKING AT GRADE IX OF SMP N 3 TEMBILAHAN - Dela, Ica; Amri, Samsul; Purwanti, Sri Erma (Program Studi Pendidikan Bahasa Inggris, 2023)
Students’ interest is one of the psychological problems. Interest has an important role in successful learning. The students’ interest will make the students active and pay more attention in speaking learning process. Interest will be forced the students to learn and practice it. The purpose of these research is to identify if there is correlation between students’ Activities in Storytelling with their Interest in speaking and to identify how the correlation between students’ activities in storytelling with their interest in speaking at grade IX of SMPN 3 Tembilahan. In selecting a sample, the researcher used “Cluster Random Sampling” by choosing one classes. This research method is a quantitative descriptive method. Based on the score of product moment by using SPSS window program, rxy is (0,99), it shows there is Very High correlation between students’ activities in Storytelling with their Interest in speaking. Alternative hypothesis rxy in the significant 5% rtable is accepted, because rxy =0,99 is higher than rtable =0,35, so there is correlation between students’ activities in Storytelling with their Interest in speaking. There is an intervening variable that makes the correlation is Very High. It comes from the Preparation before perform Storytelling. Based on the data analysis, it can be concluded that there is Very High significant correlation between students’ activities in Storytelling with their Interest in speaking.